2006
DOI: 10.1002/jor.20045
|View full text |Cite
|
Sign up to set email alerts
|

Forces and torques during fracture reduction: Intraoperative measurements in the femur

Abstract: Reduction is a crucial step in fracture treatment. We determined intraoperative peak forces and torques during fracture reduction in seven patients with eight fractures of the femoral shaft. All fractures were temporarily stabilized by external fixation. Force and torque measurements were performed during the subsequent intramedullary nailing procedure. A three-dimensional load cell was attached to the distal femur fragment using two Schanz screws. All forces and torques were registered on-line during the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
0
43
1
Order By: Relevance
“…Previous studies have reported on applied fracture reduction forces. G€ osling et al [5] used a six-DOF sensor, rigidly fixed to an external fixator tube connected to the distal fragment through two Schanz screws, to collect and transmit reduction forces and torques. The opposite surface of the sensor was attached to a bar with two handles, used for alignment of the fracture fragments.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported on applied fracture reduction forces. G€ osling et al [5] used a six-DOF sensor, rigidly fixed to an external fixator tube connected to the distal fragment through two Schanz screws, to collect and transmit reduction forces and torques. The opposite surface of the sensor was attached to a bar with two handles, used for alignment of the fracture fragments.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…All reductions were performed under radiographic monitoring ( Figure 5). [5] Femoral shaft fractures were classified using the AO/ASIF system, with typical diaphyseal femoral fractures (type A1-spiral, A2-oblique and A3-transverse) included in our study. Standard aseptic procedures were performed prior to using the measurement instrument.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed in part to the reduction table which is limiting in the degrees of freedom (DoF) and obtainable accuracies combined with mental strain from reconstructing images in 3-D. The manual traction interface to carry out the operation requires the surgeon to exert forces to counteract reduction which have been reported between 201 and 411 Newtons (Maeda et al, 2005;Gösling et al, 2006) and can lead to physical fatigue. Radiation reduction is a contributing motivator for a number of medical robotic research projects (Loser & Navab, 2000;Stoianovici et al, 2003;Cleary et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Very recent studies concerned intra-operative measurement procedures (Jenkinson et al, 2005;Gosling et al, 2006), and this endeavoured to answer the need to better identify and quantify the clinical gesture. The clinical relevance of our approach has fallen in this framework relating to maxillofacial pathologies and more particularly proptosis reduction.…”
Section: Introductionmentioning
confidence: 99%